A new insular species of Gehyra (Squamata: Gekkonidae) from Papua New Guinea closely related to Gehyra oceanica - Kraus, Fred; Vahtera, Varpu; Weijola, Valter (Taylor & Francis, 2025)
The wide-ranging gecko Gehyra oceanica occupies numerous islands across much of the Pacific Ocean basin. Previous work has identified six divergent genetic lineages within lizards assigned to this species. During an expedition to islands off of northern New Guinea we collected lizards of this complex on Crown Island that differ from all other known Gehyra in being sexually dimorphic in colour pattern. We find this population to also be genetically divergent to the other lineages previously identified, as we do with another lineage of populations from nearby islands. Given the unique colour pattern of the Crown Island population, combined with its divergent range of precloacal-femoral pores in males and its phylogenetic uniqueness from other members of this complex, we describe this population as a new species, Gehyra corona sp. nov. currently known only from Crown Island, Papua New Guinea. The discovery of this new species and an additional divergent genetic lineage from within the G. oceanica complex highlights the need for further taxonomic revision of that species complex. It seems likely that the new species we identify will prove endemic to Crown Island, but additional islands from around the Bismarck Sea need survey to establish its full range. Given the undisturbed habitat on most of Crown Island and the low human population there, we suggest that this species’ IUCN Red List conservation status be Least Concern.